Preparation for the next pandemic: challenges in strengthening surveillance - Kelvin Hei-Yeung Chiu; Siddharth Sridhar; Kwok-Yung Yuen (Emerging Microbes and Infections, 2023)
The devastating Coronavirus Disease 2019 (COVID-19) pandemic indicates that early detection of candidates with pandemic potential is vital. However, comprehensive metagenomic sequencing of the total microbiome is not practical due to the astronomical and rapidly evolving numbers and species of micro-organisms. Analysis of previous pandemics suggests that an increase in human–animal interactions, changes in animal and arthropod distribution due to climate change and deforestation, continuous mutations and interspecies jumping of RNA viruses, and frequent travels are important factors driving pandemic emergence. Besides measures mitigating these factors, surveillance at human–animal interfaces targeting animals with unusual tolerance to viral infections, sick heathcare workers, and workers at high biosafety level laboratories is crucial. Surveillance of sick travellers is important when alerted by an early warning system of a suspected outbreak due to unknown agents. These samples should be screened by multiplex nucleic acid amplification and subsequent unbiased next-generation sequencing. Novel viruses should be isolated in routine cell cultures, complemented by organoid cultures, and then tested in animal models for interspecies transmission potential. Potential agents are candidates for designing rapid diagnostics, therapeutics, and vaccines. For early detection of outbreaks, there are advantages in using event-based surveillance and artificial intelligence (AI), but high background noise and censorship are possible drawbacks. These systems are likely useful if they channel reliable information from frontline healthcare or veterinary workers and large international gatherings. Furthermore, sufficient regulation of high biosafety level laboratories, and stockpiling of broad spectrum antiviral drugs, vaccines, and personal protective equipment are indicated for pandemic preparedness.